Path to practising self‐compassion in a tertiary eating disorders treatment program: A qualitative analysis. (12th April 2022) - Geller, Josie; Fernandes, Avarna; Srikameswaran, Suja; Pullmer, Rachelle; Marshall, Sheila
Abstract: Objective: Although self‐compassion has been shown to facilitate eating disorder (ED) remission, significant barriers to acquiring this skill have been identified. This is particularly true for tertiary care populations, where ED behaviours provide a valued identity and readiness issues are highly salient. In this research, the voices and perspectives of patients who have recovered as well as those in later stages of tertiary care treatment were captured using qualitative methods. Methods: Seventeen individuals with a lengthy ED history (seven fully recovered, 10 currently in recovery‐focused residential treatment) participated in audio recorded interviews. Using a visual timeline, participants described the development of their understanding of self‐compassion, barriers to self‐compassion and how these barriers were overcome. Results: Three processes were identified, reflecting different levels of readiness. Challenging my beliefs involved overcoming cognitive barriers to the concept of self‐compassion (i.e. coming to see self‐compassion as helpful), and set the stage for dealing with the world around me and rolling up my sleeves, which reflected preparatory (i.e. freeing oneself from difficult life circumstances) and active (i.e. having the courage to do the work) change efforts, respectively. Conclusions: These findings may help patients embarking on tertiary care treatment to envision a roadmap of supportive processes and help clinicians tailor interventions to patient level of readiness for self‐compassion.